The effects of burial diagenesis on multiscale porosity in the St. Peter Sandstone: An imaging, small-angle, and ultra-small-angle neutron scattering analysis. (April 2018) - Anovitz, Lawrence M.; Freiburg, Jared T.; Wasbrough, Matthew; Mildner, David F.R.; Littrell, Kenneth C.; Pipich, Vitaliy; Ilavsky, Jan
Abstract: To examine the effects of burial diagenesis on heirarchical pore structures in sandstone and compare those with the effects of overgrowth formation, we obtained samples of St. Peter Sandstone from drill cores recovered from the Illinois and Michigan Basins. The multiscale pore structure of rocks in sedimentary reservoirs and the mineralogy associated with those pores are critical factors for estimating reservoir properties, including fluid mass in place, permeability, and capillary pressures, as well as geochemical interactions between the rock and the fluid. The combination of small- and ultra-small-angle neutron scattering with backscattered electron imaging, provided a means by which pore structures were quantified at scales ranging from approximately 1 nm to 1 cm—seven orders of magnitude. Larger scale (>10 μm) porosity showed the expected logarithmic decrease in porosity with depth, although there was significant variation in each sample group. However, small- and ultra-small-angle neutron scattering data showed that the proportion of small-scale porosity increased with depth. Porosity distributions were not continuous, but consisted of a series of log normal-like distributions at several distinct scales within these rocks. Fractal dimensions at larger scales decreased (surfaces smoothed) with increasing depth, and those at smaller scales increased (surfaces roughened) and pores become more isolated (higher lacunarity). Data suggest that changes in pore-size distributions are controlled by both physical (compaction) and chemical effects (precipitation, cementation, dissolution). Highlights: Volume of pores >10 μm decreases with depth, but the fraction of small-scale porosity increases. Porosity distributions form log normal-like distributions at several distinct scales. Data suggest that a significant fraction of the pores are on grain faces rather than edges. Fractal dimensions at larger scales decrease with depth whereas those at smaller scales increase. Pores become more isolated (higher lacunarity) but overall surface area increases with depth.